An Application Of Solar Power Plant (PLTS) As Power Supply For Radio Repeater Pt. Icon Plus Pekan Baru - Khairunnisa Salsabila Purba; Amani Darma Tarigan; Ahmad Dani (Jurnal Scientia, 2024)
In the utilization of Radio Repeater communication, electrical energy is needed to supply the radio so that communication can always run well. The problem is that there are frequent power outages that disrupt information activities via radio communication. Frequent power outages from PLN cause the Radio Repeater to be inactive so that communication is cut off. Therefore, in this study, a Solar Power Plant (PLTS) is utilized as a power supply for the Radio Repeater at PT. Icon Plus Pekanbaru to be able to operate non-stop and be able to survive for at least 3 days without sunlight. The maximum power generated by the solar panel is 6 panels x 100 Watt = 600 Watt. The amount of energy generated = The amount of power generated (watts) x Peak Sun Hours (hours) or Wh = 600 x 4 = 2400. The radio repeater operating time is 10 hours per day. Two 40 watt lighting lamps operate with the assumption that the condition is on for 13 hours per day. The lights are on from 6 pm to 7 am. Radio Load = Current Consumption (A) x Usage Time (hour) x System Voltage (V), Active Radio = 6 x 10 x 12 = 1440, Radio on standby = 1.5 x 12 = 864, Lighting = 13 x 40 = 520. then the difference between production energy and used energy is 1920 Wh - 1672 Wh = 248 Wh. With a configuration of two 200 Ah batteries in parallel with a DoD assumption of 50%, the Days of Autonomy can be calculated by ((50% x 600 x 12) + 248 Wh) / 1672 Wh = 2.3 days